2019
DOI: 10.1016/j.heliyon.2019.e02134
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Russian version of the Pediatric Daytime Sleepiness Scale (PDSS)

Abstract: Insufficient sleep could severely impair both cognitive and learning skills. More prominent changes are found in children and adolescents. Tools used to estimate sleepiness in the adult population are commonly inappropriate for children. The objective of our study was to provide a reliable instrument to measure excessive sleepiness for upcoming studies in Russian-speaking children, applying the Russian version of Pediatric Daytime Sleepiness Scale (PDSS). The following tasks were resolved in our study: transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…Before discussing these findings further, it is important to address the issue of whether the PDSS score is a valid reflection of daytime sleepiness in elementary school children. The validity of this measure has been confirmed in middle school children aged 11–15 years [ 2 ], and it is known to be a suitable tool for evaluating child sleepiness [ 3 , 19 , 20 ]. Although the PDSS has not been specifically validated in samples younger than 11 years of age, there is no reason to question its ability to detect sleepiness in children of school age (>5 years), provided that the individual has sufficient reading skills [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before discussing these findings further, it is important to address the issue of whether the PDSS score is a valid reflection of daytime sleepiness in elementary school children. The validity of this measure has been confirmed in middle school children aged 11–15 years [ 2 ], and it is known to be a suitable tool for evaluating child sleepiness [ 3 , 19 , 20 ]. Although the PDSS has not been specifically validated in samples younger than 11 years of age, there is no reason to question its ability to detect sleepiness in children of school age (>5 years), provided that the individual has sufficient reading skills [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…All participants and their parents were informed about the aims of the study prior to enrollment, and written informed consent was obtained from the parent or legal guardian before being administered the survey. A validated Russian version of the PDSS, 27 and the Munich Chronotype Questionnaire (MCTQ), 31 were distributed to the participants in paper form. Monthly family income evaluation was done according to Russian Household Income Report.…”
Section: Methodsmentioning
confidence: 99%
“…The Pediatric Daytime Sleepiness Scale (PDSS) is an 8-item questionnaire that assesses EDS in school children and adolescents; the questionnaire was translated into Russian. 27 These authors established the reliability and validity of the scale by exploratory and confirmatory factor analyses and Cronbach’s alpha, as well as by test–retest reliability. The 5-point Likert scale ranges from 0 (never) to 4 (always).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the ESS has been described as a unidimensional 8-scale by its developer [35] and other authors from different settings [8,17,18]. Few studies reported extracting two factors though, such as a study that assessed an Arabic ESS version among students in Sudan [15] and an Iranian version that was tested among patients with sleep disorders [37].…”
Section: Discussionmentioning
confidence: 99%
“…The Epworth Sleepiness Scale (ESS), a subjective assessment tool, was first developed in 1990 [2] and modified in 1997 to assess EDS among adults [3]. Since then, the scale has been used in general [4] and clinical populations [5,6] and was effectively adapted to children and adolescents [7,8].…”
Section: Introductionmentioning
confidence: 99%